The human gut metacommunity as a conceptual aid in the development of precision medicine - Tannock, Gerald W. (Frontiers in Microbiology, 2024)
Human gut microbiomes (microbiotas) are highly individualistic in taxonomic 16 composition but nevertheless are functionally similar. Thus, collectively, they comprise 17 a “metacommunity”. In ecological terminology, the assembly of human gut microbiomes 18 is influenced by four processes: selection, speciation, drift, and dispersal. As a result of 19 fortuitous events associated with these processes, individual microbiomes are 20 taxonomically “tailor-made” for each host. However, functionally they are “off-the-shelf” 21 because of similar functional outputs resulting from metabolic redundancy developed in 22 host-microbe symbiosis. Because of this, future microbiological and molecular studies 23 of microbiomes should emphasise the metabolic interplay that drives the human gut 24 metacommunity and that results in these similar functional outputs. This knowledge will 25 support the development of remedies for specific functional dysbioses and hence 26 provide practical examples of precision medicine.